Signaling Pathways Mediating Chemokine Induction in Keratinocytes by Cathelicidin LL-37 and Flagellin - Nijnik, Anastasia (J Innate Immun, 2012)
Cathelicidin LL-37 is a multifunctional immunomodulatory and antimicrobial host defense peptide that has an important role in the immune defenses of the skin and other epithelial barriers. We have previously demonstrated that at physiological concentrations LL-37 synergistically augments the production of immune mediators in response to microbial compounds in human primary keratinocytes. Here we define the signaling mechanisms responsible for this activity. We demonstrate that inhibition of Src family kinases (SFKs) strongly inhibited the synergistic chemokine production in response to LL-37 and flagellin in keratinocytes. SFK activation was induced by LL-37 stimulation and was required for the downstream activation of Akt (protein kinase B) and the transcription factors CREB and ATF1. In cells stimulated with LL-37 and flagellin together, Akt activation was primarily induced by LL-37, while both flagellin and LL-37 contributed to the activation of CREB and ATF1 and consequently chemokine induction. The purinergic receptor P2X(7) was identified as the receptor upstream of SFK activation in LL-37-stimulated keratinocytes. Overall, these findings established the P2X(7)–SFK–Akt–CREB/ATF1 signaling pathway activated by LL-37 in primary keratinocytes. These signaling mechanisms mediated the synergistic effects of LL-37 on chemokine production in flagellin-stimulated keratinocytes, and thus might have a role in the immune defenses of the skin and possibly other epithelial barriers.